AI and Blockchain in Cybersecurity: A Sustainable Approach to Protecting Digital Assets - Mohamed, Sheik; M, Nirmala; N, Theerka; Dennison J, Evans; Hermansyah, Sam (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study explores the integration of Artificial Intelligence (AI) and Blockchain technologies to enhance cybersecurity. AI, with its advanced machine learning and deep learning models, significantly improves threat detection and response times. By learning from data and adapting to new threats, AI offers faster and more accurate detection of malware and zero-day attacks. Blockchain, on the other hand, ensures data integrity through its decentralized and tamper-proof architecture, making it highly effective in safeguarding sensitive information, particularly in sectors such as healthcare and finance. The study examines the combined benefits of AI and Blockchain, focusing on real-world applications like the UK's National Health Service and Google DeepMind collaboration. Despite the promising potential, the implementation of these technologies faces challenges including data privacy concerns, a lack of technical expertise, infrastructure limitations, and regulatory uncertainties. The study emphasizes the need for further research, stronger regulatory frameworks, and enhanced digital literacy to fully realize the potential of AI and Blockchain in creating a secure and resilient digital infrastructure. Recommendations include the development of hybrid models combining AI and Blockchain, the adoption of Blockchain in critical sectors, and fostering public-private partnerships to accelerate technological integration. Ultimately, AI and Blockchain together present a sustainable solution for combating cyber threats and securing digital ecosystems.